2010
DOI: 10.1007/s00775-010-0748-5
|View full text |Cite
|
Sign up to set email alerts
|

X-ray absorption spectroscopy studies of the adducts formed between cytotoxic gold compounds and two major serum proteins

Abstract: Gold metallodrugs form a class of promising antiproliferative agents showing a high propensity to react with proteins. We exploit here X-ray absorption spectroscopy (XAS) methods [both X-ray absorption near-edge spectroscopy (XANES) and extended X-ray absorption fine structure (EXAFS)] to gain insight into the nature of the adducts formed between three representative gold(I, III) metallodrugs (i.e., auranofin, [Au(2,2'-bipyridine)(OH)(2)](PF(6)), Aubipy, and dinuclear [Au(2)(6,6'-dimethyl-2,2'-bipyridine)(2)(μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
19
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 42 publications
5
19
0
2
Order By: Relevance
“…29 Data are also in agreement with the fact that gold(I) centers are anchored to the protein mainly through nitrogen donors. 30 Aubipy c reduction and gold(I) binding to proteins is consistent with the observation that this molecule is able to inhibit mitochondrial thioredoxin reductase, producing apoptotic cell death. 31 In a more general framework, these data reveal that the formed HEWL−gold adducts are distinct when different goldbased bioactive agents react with the same protein (compare data reported in ref 6 and the present work), although the metallodrug−protein reactions invariantly lead to formation of Au(I) ions.…”
supporting
confidence: 85%
See 1 more Smart Citation
“…29 Data are also in agreement with the fact that gold(I) centers are anchored to the protein mainly through nitrogen donors. 30 Aubipy c reduction and gold(I) binding to proteins is consistent with the observation that this molecule is able to inhibit mitochondrial thioredoxin reductase, producing apoptotic cell death. 31 In a more general framework, these data reveal that the formed HEWL−gold adducts are distinct when different goldbased bioactive agents react with the same protein (compare data reported in ref 6 and the present work), although the metallodrug−protein reactions invariantly lead to formation of Au(I) ions.…”
supporting
confidence: 85%
“…In fact, it is known that this latter solvent is capable of providing reducing species, without the need for a separate reducing agent. 28 X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS) studies carried out on AubipyOH ([Au(2,2′-bipyridine)(OH)2](PF 6 )), in complex with bovine serum albumin, 29,30 showed that the protein-bound gold center manifests a lower coordination number than in AubipyOH alone, strongly suggesting that gold(III) to gold(I) reduction has occurred upon protein interaction. 29 Data are also in agreement with the fact that gold(I) centers are anchored to the protein mainly through nitrogen donors.…”
mentioning
confidence: 99%
“…Thus, the precise knowledge of the interactions occurring between medicinal gold compounds and proteins seems crucial to understand in depth their mode of action; indeed this class of molecules are believed to be activated upon protein interaction (de Almeida et al 2013;Cinellu et al 2015) and then to exert their biological actions by hitting and damaging selectively a few protein targets. Although several papers have already described the interactions of gold compounds with proteins (Bhabak et al 2011;Messori et al 2011;Gabbiani et al 2012), only few structural studies have appeared so far and very few Au binding sites have been characterized in proteins (Urig et al 2006;Zhou et al 2000;Bhabak et al 2011;.…”
Section: Introductionmentioning
confidence: 99%
“…[83] While reported in the context of Au anti-proliferative agents, Messori et al recently performed XAS studies of the interactions of auranofin with the human plasma proteins, bovine serum albumin and serum apotransferrin. [84] The Au(I) oxidation state was conserved during protein binding and the mechanism was believed to occur through release of the thiosugar ligand to facilitate replacement with a thiol or thioether from the protein. [84] The use of XAS for the development of copper containing NSAIDs, such as nonsteroidal anti-inflammatory formulations, the latter proceeding to human clinical trials.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…[84] The Au(I) oxidation state was conserved during protein binding and the mechanism was believed to occur through release of the thiosugar ligand to facilitate replacement with a thiol or thioether from the protein. [84] The use of XAS for the development of copper containing NSAIDs, such as nonsteroidal anti-inflammatory formulations, the latter proceeding to human clinical trials. [85] XAS was used to explore the chemical and physical properties of the formulations with emphasis on modelling the dimeric Cu 2 O 10 C 8 core in the dimeric Cu(II) complex and examining any changes in it as a result of changes in the axial ligands.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%